Fluorescence and Opalescence of Two Dental Composite Resins - Tabatabaei, Masoomeh Hasani; Nahavandi, Alireza Mahmoudi; Khorshidi, Sotude; Hashemikamangar, Sedighe Sadat (European Journal of Dentistry, 2019)
Objective Lifelike esthetic appearance of dental restorations is among the main goals in restorative dentistry. This study aimed to assess and compare the opalescence and fluorescence of two dental composite resins.Materials and Methods This in vitro experimental study evaluated the A2 shade of Filtek Z350 XT Enamel, Filtek Z350 XT Dentin, Aelite Aesthetic Enamel, and Aelite All Purpose Body composite resins. Composite discs were fabricated with 10 mm diameter and 0.5 and 1 mm thicknesses (n = 2) using a plexiglass mold and subjected to colorimetry. The color parameters were determined according to the International Commission on Illumination (CIE) L*a*b* system using a spectrophotometer. The fluorescence and opalescence were also measured and reported separately for 0.5 and 1 mm thicknesses of Z350, Aelite Body, and Enamel composite resins. To determine the opalescence, the color of samples in the reflectance mode was measured using a calibration cylinder and in the transmittance mode in presence of 100% ultraviolet (UV) light. To determine the fluorescence, the color of samples against a white background in the reflectance mode in presence or absence of 100% UV light was measured.Statistical Analysis Data were analyzed using SPSS via three-way analysis of variance and independent t-test.Results The fluorescence of 0.5 mm thickness of all composites was higher than that of 1 mm thickness (p < 0.05). The fluorescence of Aelite was higher than that of Z350 (p < 0.05). The fluorescence of Aelite Enamel was higher than that of Aelite Body irrespective of their thickness, but the results were opposite for Z350 (p < 0.05). In Aelite composite, opalescence increased by an increase in thickness (p < 0.05). The opalescence of Aelite was significantly higher than that of Z350 (p < 0.05). The opalescence of 0.5 mm thickness of Aelite Enamel was higher than that of Aelite Body, while the opalescence of 1 mm thickness of Z350 Body was higher than that of Z350 Enamel (p < 0.05).Conclusion Thickness, type, and brand of composite resins affected their fluorescence and opalescence.
Keywords: composite resins; fluorescence; opalescence; spectrophotometry